Pelaksanaan Gugatan Sederhana di Pengadilan Negeri dalam Perspektif Kepastian Hukum - Sri Nurcahyani (Fakultas Hukum Universitas Boyolali, 2023)
Simple lawsuits in Indonesia are used formally in the Supreme Court Regulation of the Republic of Indonesia Number 4 of 2019 concerning Amendments to Supreme Court Regulation Number 2 of 2015 concerning Procedures for Settlement of Simple Claims (PERMA Number 4 of 2019), which is a provision of Article 1 point 1. A simple lawsuit is defined as a settlement procedure in civil cases with certain conditions and limitations that aim to simplify the process of examining cases before a court of law so that the settlement is faster and is specifically applied to contract disputes (default/default) and claims for losses due to unlawful acts. . The general principle in settling a case in court is as explained in Article 2 paragraph (4) of Law Number 48 of 2009 concerning Judicial Power which requires that trials be carried out simply, quickly and at low cost. This study aims to find out about the implementation of simple lawsuits in the District Court from the perspective of legal certainty. The research method used is descriptive analysis with a normative juridical approach. The sources of data used in this research are primary, secondary, and tertiary legal materials. All data obtained and collected is then used and understood the truth that has been obtained from research results to look for relationships between one another